The strong cultural and religious values embraced by the Madura community also affect the strong emotional relations between society and family. Most of the people in Madura stated that among them, they still know each other and were very close to their f - Arna, Yessy Dessy; Asnani, Asnani (International Journal of Psychosocial Rehabilitation, 2020)
The strong cultural and religious values embraced by the Madura community also affect the strong emotional relations between society and family. Most of the people in Madura stated that among them, they still know each other and were very close to their families for up to three generations. The purpose of this study was to illuminate the lived experiences related to the Madurese perception of their family member’s illness condition. A purposive sample was taken of 23 Madurese individuals. Semi-structured interviews were conducted over the Madura region. Three key themes were found from the data analysis: the definition of family, the social factors, family attachment, and the concept of illness. The closeness between families across the three generations makes them feel responsible for giving attention to others, in both a healthy or sick condition, and regardless of whether or not they are rich or poor. The focus between them remains well-maintained. It proves that if one of the family members is ill, they feel the need to be "reinforcements" for that person. The family members will take the ill person to the hospital together and provide them with a feeling of "reinforcements." All of the family members will stay in the hospital to accompany and treat the sick one.